Multilingualism and Identity in Algerian University Classrooms: A Theoretical Review of Language Use Intercultural Competence - Rabahi, Hanane; Makhlouf, Abdelkader (Journal of Ecohumanism, 2026)
Within Algeria’s plural higher education system, university classrooms are mini-scale models of large-scale identity, political, and sociocultural processes. They are anything but passive spaces for knowledge transmission but spaces where Arabic, Tamazight, French, and increasingly English cross, clash, and coexist, articulating old histories of colonialism, Arabization policies, and globalization. To this purpose, multilingual practice is found to lie at the centre of how teachers and students negotiate identity, access symbolic capital, and move between visions of global and national belonging in conflict. This article employs a descriptive-analytical methodology to synthesize existing literature on patterns of multilingualism, identity negotiation, language policy, and intercultural competence within Algerian university contexts. Based on theoretical frameworks such as Norton’s (2000) investment theory of identity and Byram’s (1997) intercultural communicative competence framework, the research questions and examines how multilingual practices are being made, contested, and negotiated simultaneously by learners and teachers. Defining themes such as pedagogic strategies, policy tensions, symbolic and functional functions of language, and requirements for curriculum reform are codified through investigation. The review also mentions a taken-for-granted gap between theoretical monolingual or bilingual policy and practical classroom multilingual practice, where hybridity, flexible repertoires, and code-switching orchestrate daily interaction. The pedagogic consequence of these findings is significant for the pedagogy of translation and intercultural education and requires an inclusive language policy, teacher training modules in pedagogy of multilingualism, and culture-full, rich curricula. Last but not least, the paper argues that it is in seizing the pedagogical value of multilingualism as capital rather than deficit that more socially aware, cosmopolitan, and inclusive Algerian higher education can be constructed.